Regulating COX10-AS1 / miR-142-5p / PAICS axis inhibits the proliferation of non-small cell lung cancer. Issue 1 (1st January 2021) - Tang, Xinyu; Wu, YiHe; Yang, Jie; Zhu, Wenyu
ABSTRACT: Non-small cell lung cancer (NSCLC) is one of the main causes of death in the world. To improve the diagnostic level and find new biological targets，GSE datasets were selected from GEO databaseto analyze the differential expression genes and construct ceRNA network. Cell apoptosis detection showed that both the early and late apoptosis rates were increased after inhibition of COX10-AS1. Glycolysis cell-based assay also found that the content of L-lactate decreased significantly after using miR-142-5p mimics but increased after using si-COX10-AS1. Dual-luciferase reporter analysis showed that the luciferase activity of PAICS-WT reporter vector was inhibited by miR-142-5p mimics, but there was no significant change in PAICS-MUT reporter vector after transfection of miR-142-5p mimics. And overexpression of miR-142-5p reduced the level of PAICS, but inhibition of miR-142-5p expression increased the expression of PAICS. After using COX10-AS1, the expression of PAICS inhibited by miR-142-5p was restored. Through bioinformatics analysis, we constructed the COX10-AS1/miR-142-5p/PAICS axis, which is a ceRNA regulatory network. We confirmed that COX10-AS1 down-expression can restore the inhibitory effect of miR-142-5p on PAICS, promote the apoptosis of NSCLC cells, and inhibit the proliferation of NSCLC cells. This process may be mediated by the activation of glycolysis pathway. The glycolysis-related gene PAICS may be a new and significant target for the regulation of the development of NSCLC.